Resonant selves in ethical and theological perspective: On personhood and identity formation. Issue 4 (12th January 2022) - Gregersen, Niels Henrik
Abstract: Absorbing insights from secular discourses on personhood, theology can provide added perspectives on human identity. (1) An attributive view of personal dignity based on divine and social recognition encompasses both capacity‐oriented and relation‐centred views of personhood. (2) Gregory of Nyssa shows Patristic resources for multifaceted ecological self in some contrast to the inner‐Trinitarian idea of ecclesial persons in John D. Zizioulas. (3) An economic Trinitarian model of personhood is proposed, in which the indwelling of Christ is balanced by a pneumatological anthropology. (4) Entering contemporary discussions, the paper proposes a "sonar" or "re‐sonant" understanding of the human per‐sona, hereby accommodating and responding to particularistic challenges to the idea of a shared human personhood.